The Baltics : Competitiveness on the Eve of EU Accession - Xiao, Yuan (International Monetary Fund, 2004)
Large current account deficits in Estonia and Latvia, and the continued real appreciation of the exchange rate in Lithuania, have prompted concerns about the competitiveness of the Baltic economies, and called into question the sustainability of their current fixed exchange rate arrangements. Recent external performance, however, appears to be explained more by temporary or cyclical developments than by a deterioration in the underlying competitive position of the Baltic economies. This book assesses the competitive position of the Baltic countries and focuses, in particular, on the viability of the countries' strategy of maintaining their fixed exchange rates on joining the European Union, participating in its exchange rate mechanism, and then adopting the euro at the earliest possible date.